Peningkatan Kedisiplinan Siswa dengan Metode Layanan Bimbingan dan Konseling Individu pada Siswa Kelas VIII - Suryani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This research is entitled "Improving Student Discipline through Individual Guidance and Counseling Services for Eighth Grade Students." The research subjects are students from class VIII A at SMP Muhammadiyah 3 Karangpandan during the academic year 2022/2023. The objectives of this study are: (1) To determine the discipline condition of the seventh-grade students of SMP Muhammadiyah 3 Karangpandan before receiving individual guidance and counseling services, (2) To understand how the method of individual guidance and counseling services can improve the discipline of the eighth-grade students of SMP Muhammadiyah 3 Karangpandan, and (3) To identify the results of the improvement in discipline of the eighth-grade students of SMP Muhammadiyah 3 Karangpandan after receiving individual guidance and counseling services. Based on the desired aspects, the Classroom Action Research (CAR) method is employed in this study because it is generally suitable for improving the quality of the research subject. According to the research findings, it was observed that individual guidance and counseling services can enhance student discipline in their learning process.